Особенности фотоэлектрических характеристик фотоэлектропреобразовательных структур - Karimov, A. V.; Yodgorova, D. M.; Giyasova, F. A.; Azimov, T. M.; Buzrukov, U. M.; Yakubov, A. A. (PE "Politekhperiodika", Book and Journal Publishers, 2007)
The peculiarities of photoelectric characteristics of converter structures based on the isotype n-GaAs/n-GaInAs heterojunction with Ag potential barriers have been investigated. The physical processes occurring in the potential barriers under optical irradiation are analyzed. The structures exhibit enhanced photosensitivity (2.2 A/W) at low light intensities. The photocurrent in the impurity absorption region covers a wide spectral range, extending up to 1.7 μm.